2014
DOI: 10.3389/fnana.2014.00055
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cajal's view of the olfactory system

Abstract: The olfactory system has a highly regular organization of interconnected synaptic circuits from the periphery. It is therefore an excellent model for understanding general principles about how the brain processes information. Cajal revealed the basic cell types and their interconnections at the end of the XIX century. Since his original descriptions, the observation and analysis of the olfactory system and its components represents a major topic in neuroscience studies, providing important insights into the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…The OB is composed of two distinct structures: the main (MOB) and accessory olfactory bulb (AOB). Albeit sharing some common cytological organization with similarly named neurolamina -nomenclature that was carried forward from the MOB to the AOB by Ramon y Cajal (Figueres-Onate et al 2014) -there are several noteworthy differences in the organization of AOB cell types whose biophysical analyses are largely incomplete. A prominent difference lies in the principal output neurons, called mitral cells (MCs), in both systems.…”
Section: Introductionmentioning
confidence: 99%
“…The OB is composed of two distinct structures: the main (MOB) and accessory olfactory bulb (AOB). Albeit sharing some common cytological organization with similarly named neurolamina -nomenclature that was carried forward from the MOB to the AOB by Ramon y Cajal (Figueres-Onate et al 2014) -there are several noteworthy differences in the organization of AOB cell types whose biophysical analyses are largely incomplete. A prominent difference lies in the principal output neurons, called mitral cells (MCs), in both systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, the linear Aβ signal could be detected in the axonal bundles between OE cells. This may be attributed to the olfactory cells being bipolar neurons which congregate to form the olfactory nerve among supporting cells . In contrast, other AD‐like mouse models exhibit different OE involvement by Aβ peptide, appearing as Aβ‐positive puncta in the basal cell layer .…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the olfactory cells being bipolar neurons which congregate to form the olfactory nerve among supporting cells. 19 In contrast, other AD-like mouse models exhibit different OE involvement by Aβ peptide, appearing as Aβ-positive puncta in the basal cell layer. 20 In addition, Aβ toxicity contributes to the increased apoptotic cells labeled positively with TUNEL staining in the superficial or middle layer of OE and finally lead to the atrophy of OE.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the structure of the rodent OB as an anatomical model for reference. Although we do not go deeper into detail in this review, there are many excellent reviews summarizing the cell types, synapses, and neuronal circuits found in the MOB ( Shepherd et al, 2004 ; Wachowiak and Shipley, 2006 ; Figueres-Onate et al, 2014 ; Imai, 2014 ; Nagayama et al, 2014 ; Sakano, 2020 ). Briefly, the OSN axons run tangentially through the olfactory nerve layer (ONL) at the surface of the OB before entering the glomerular layer (GL) ( Klenoff and Greer, 1998 ; Rodriguez-Gil et al, 2015 ).…”
Section: Basic Neural Circuitry Of the Mammalian Olfactory Systemmentioning
confidence: 99%